Physical variables - lake profile additional logger system from Almbergasjön, limnic profile - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2023)
High frequency additional logger system measurements of CO2 and/or O2 along a depth profile in the lakes of SITES Water.
Abisko Scientific Research Station (2023). Physical variables - lake profile additional logger system from Almbergasjön, limnic profile, 2017-06-21–2017-10-05 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/qJ6sCxO-M4fxiRCPaDCx729u
Keywords: Abisko Scientific Research Station; Carbon dioxide; Oxygen; Time instant; Time instant; Water depth; Water depth; Water temperature; Water temperature; Specific conductivity; Specific conductivity; Dissolved oxygen; Dissolved oxygen; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap